2015
DOI: 10.1155/2015/538254
|View full text |Cite
|
Sign up to set email alerts
|

Impact Analysis of Window-Wall Ratio on Heating and Cooling Energy Consumption of Residential Buildings in Hot Summer and Cold Winter Zone in China

Abstract: In order to assess the optimal window-wall ratio and the proper glazing type in different air conditioning system operation modes of residential buildings for each orientation in three typical cities in hot summer and cold winter zone: Chongqing, Shanghai, and Wuhan simulation models were built and analyzed using Designer’s Simulation Toolkit (DeST). The study analyzed the variation of annual heating energy demand, annual cooling energy demand, and the annual total energy consumption in different conditions, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 16 publications
(15 reference statements)
1
19
0
Order By: Relevance
“…The works of Carriere, et al [20], Huang, et al [11], Yang, et al [21] and Vanhoutteghem, et al [22] investigated the effectiveness of different glazing and window design systems under different climates with the aid of building simulation software. Huang, et al [11] examined the efficacy of different Sustainability 2017, 9, 731 4 of 23 energy-efficient building window designs in a cooling-dominant climate.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The works of Carriere, et al [20], Huang, et al [11], Yang, et al [21] and Vanhoutteghem, et al [22] investigated the effectiveness of different glazing and window design systems under different climates with the aid of building simulation software. Huang, et al [11] examined the efficacy of different Sustainability 2017, 9, 731 4 of 23 energy-efficient building window designs in a cooling-dominant climate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the effect of important parameters such as wall-to-window ratios or shading coefficients on solar heat gain in the building was not investigated in that research. Yang, et al [21] investigated the optimal window-wall ratio and the adequate glazing type in varied air-conditioning system operation modes of domestic buildings for individual orientation in a hot summer-cold winter climate. Their results indicated that the overall energy consumption increased with an increasing window-wall ratio, especially for east-or west-oriented windows.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yang et al [88] showed that the total energy consumption would increase when the WWR is increased, as half of the energy in a building is lost through the window [89]. Thus, it is important to determine the optimal WWR for different building facades to reduce such loss [90].…”
Section: Discussionmentioning
confidence: 99%
“…Troup et al [92] demonstrated that WWR is statistically significant at most of the levels of glazing when predicting the cooling, lighting, and ventilation energy use, but they are not statistically significant for the heating load in office buildings in the US. Marino et al [93] highlighted that the optimal value of WWR is not strongly influenced by the climate conditions, and also the insulation features of the envelope does not have a strong effect on this parameter, but instead the influence of WWR on the total energy consumption are associated with the operation mode of air conditioning systems, orientation of outside windows, and the glazing types of windows [88].…”
Section: Discussionmentioning
confidence: 99%
“…Relative average disaggregated end uses and losses of energy in buildings due to the window, ventilation opening and shading is 11 percent [6,7]. Yang et al found that the total energy consumption increased when the WWR increased [10]. Nonetheless, the use of shading device as passive control system could save energy by 0.03-13.14 percent [11].…”
Section: Introductionmentioning
confidence: 99%